Export Processing Zone Development in Ethiopia: Law and Policy Review - Akalu, Mulugeta (Bahir Dar University Journal of Law, 2023)
Export processing zones [EPZs] have been used for over a century to attract investors who are interested in manufacturing and exporting. Despite long usage, the role and benefits of EPZs remain one of the most controversial areas both in practice and theory. However, the fact that countries from South East Asia and Latin America have obtained several benefits from EPZs encouraged countries such as Ethiopia to adopt them. Even though Ethiopia began its EPZs programme recently, the number of zones being built is increasing dramatically. Experience shows that the success or failure of industrial parks depends upon the host countryâ€™s condition. Most sub-Saharan African countriesâ€™ programmes of EPZs failed due to inappropriate domestic policies, regulatory systems and administration. The aim of this article was to scrutinize the impact, role, and status of Ethiopiaâ€™s export processing zones and to investigate the factors behind the success or failure of EPZs. To investigate the status of Ethiopian EPZs, the author has investigated the legal and policy frameworks of Ethiopia. Moreover, the EPZs of successful South East Asian countries and of those African countries who failed are also consulted to learn both from the success and failure stories. Using the teleological approach of comparing the realized goals against the targeted objectives, the author of this article finds that Ethiopian EPZs are not living up to their expectations. Since various factors are responsible for their underperformance, the government is advised to take numerous policy and regulatory improvements so as to reap the aspired benefits.